The Role of Social Sciences Educators in Increasing Students' Learning Motivation in The New Normal Era - Yuyun Yuningsih, Yuyun Yuningsih; Tetep; Slamet Nopharipaldi Rohman (Institut Pendidikan Indonesia, 2024)
This research is motivated by the low learning motivation of these students which can hinder the development of learning and is a threat to the progress of learning so that it must be handled appropriately. Parents and teachers are required to be able to overcome this. The research objective is to identify the efforts that can be made to realize national education goals through educational institutions known as schools. One of the subjects developed in schools is Social Sciences education. The research method used qualitative method with qualitative descriptive type, data collection techniques by observation, interviews and documentation studies. The results of the research show that the low learning motivation of students in the pandemic era made teachers determined to maximize their role as teachers in order to help students increase their learning motivation. This is not spared from the various ways that teachers use so that students' learning motivation can increase including, namely, making students active in learning activities carried out online or online, diluting the class atmosphere, making learning methods that are good and not boring, especially in learning in the new normal era as it is today.